Potencial dos frutos de Xylopia aromatica (lam.) mart. (annonaceae) no tratamento de alterações metabólicas, induzidas por dieta em camundongos balb/c - Verena Bartkowiak de Oliveira (2012)
Obesity is associated with a chronic low-grade inflammation involved in the development of various comorbidities. Studies have shown that bioactive substances in plants could modulate inflammation and improve health problems associated with the excess of adiposity. Thus, our group has studied native species from Brazil to check their potential in treating obesity and related metabolic disorders. The objective of this study was to evaluate whether the fruits of X. aromatica were able to treat obesity and modulate inflammatory and metabolic dysfunction observed in animals fed diet HC. The fruits were coldextracted until exhaustion with 95% water-alcohol solution. The extract tested was obtained after solvent evaporation. A test was performed to evaluate OGT and IS in mice after eight weeks of consumption of HC diet, or control. After confirmed the changes, the tests were repeated after four weeks of consumption of HC diet, adding the extract of the fruit at concentrations of 50, 100 and 200 mg/BW. Animals fed diet HC had higher values of adiposity and adipocyte hypertrophy, lower oral glucose tolerance and insulin sensitivity, higher HOMA-IR and lower HOMA-_, higher concentrations of TNF-_ and IL-6 in the liver and also higher values of TNF-_, IL-6 and IL-10 in the adipose tissue, compared to the animals fed with control diet. After the addition of the extract in the diet was observed improvement in oral glucose tolerance in all groups that received the extract. The group that received the extract at the highest dose also showed improvement in insulin sensitivity. The values of total leukocytes and mononuclear cell values were lower in animals supplemented with the extract, as well as the concentration of inflammatory cytokine profile (TNF-_, IL-6) in the liver. Treatment with X. aromatica improved oral glucose tolerance and insulin sensitivity, as well as systemic inflammation in the liver compared to the animals animals fed with HC diet